DATA PROTECTION METHODS IN CLOUD SYSTEMS FOR WORKING WITH ELECTRONIC DOCUMENTS - Kamoliddinova, Feruza Kamoliddin qizi; Akbarov, Navro‘z Jahongir o‘g‘li (INTERNATIONAL CONFERENCES, 2023)
Cloud computing security refers to the broad set of policies, technologies, applications, and controls used to secure virtualized IP, databases, applications, services, and cloud computing infrastructure. Protecting cloud systems is part of computer security, network security, and, more broadly, information security. Data protection is one of the most important aspects in the problem of the security of cloud systems for working with documents. To increase the security of cloud environments, enterprises need to use modern technologies and best practices to protect their data.